If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -6x + -40 = 24 Reorder the terms: -40 + 7x + -6x = 24 Combine like terms: 7x + -6x = 1x -40 + 1x = 24 Solving -40 + 1x = 24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '40' to each side of the equation. -40 + 40 + 1x = 24 + 40 Combine like terms: -40 + 40 = 0 0 + 1x = 24 + 40 1x = 24 + 40 Combine like terms: 24 + 40 = 64 1x = 64 Divide each side by '1'. x = 64 Simplifying x = 64
| -23x^2+162x-180=0 | | 14=4x-18 | | 9000000+2000000x=5000000 | | 3x+14=7x-18 | | 4x^5+x-0.1=0 | | 2=v-5 | | 9000000x=500000 | | (4+z)(4z+2)=0 | | 4x+13+7x-9-2x=8x+24-6x+7-2x | | -12y=3x-6 | | -107+2x+10x=49 | | 9x^2-40x+39=0 | | 4y+5=5y-4 | | 7+49x=28x+13 | | 4a^2e-a^2e= | | z^4+2-7i=0 | | 6x+4=19+19 | | 3x^2+17x-8=0 | | x^2=-4x+4 | | 1x+10x-97=145 | | 3-z=33 | | 9a+16=59+48 | | 3x+8=-3x-10 | | 7t+14t=0 | | 11+3x-7=18 | | 35x+28= | | -4x^2-11=17 | | 2(a-3)=2(4a-2a) | | -3x-59+8x=86 | | 18-7p=2+p | | 8x-6=7x-12 | | 5t(t-3)-8=5(t-3)(t+3) |